Learning Module Based on Brain Management and Mind Mapping to Train Mathematical Connection Abilities in Plane Geometry Course - Usdinoari, Carolina Omega Putri; Julie, Hongki (Jurnal Pendidikan MIPA, 2023)
Abstract: This research is motivated by the low level of mathematical connection ability, even though it is an important ability, also the need of teaching materials for students. In arranging teaching materials, brain management and mind mapping are used so that to help improve students' mathematical connection abilities. This research aims to develop modules based on brain management and mind mapping in plane geometry courses. The type of research used was research and development with ADDIE model. From the research that been conducted, it can be concluded that module is very valid with 91% validity from both material and media aspects, also effective as an individual learning material and for improving students’ mathematical connections in Geometry Plane Course. Keywords: mathematical connection, brain management, mind mapping, module. Abstrak: Penelitian ini dilatarbelakangi oleh rendahnya kemampuan koneksi matematis sekalipun itu adalah kemampuan yang penting, serta adanya kebutuhan bahan ajar bagi mahasiswa. Dalam penyusunan bahan ajar digunakan manajemen otak dan mind mapping agar dapat membantu meningkatkan kemampuan koneksi matematis mahasiswa. Penelitian ini bertujuan untuk mengembangkan modul berbasis manajemen otak dan mind mapping pada mata kuliah geometri bidang. Jenis penelitian yang digunakan adalah penelitian pengembangan model ADDIE. Dari penelitian yang dilakukan diperoleh bahwa modul sangat valid dengan 91% kevalidan dari kedua aspek materi dan media, serta efektif sebagai bahan belajar pribadi dan untuk meningkatkan kemampuan koneksi matematis mahasiswa pada mata kuliah Geometri Bidang.  Kata kunci: koneksi matematis, manajemen otak, mind mapping, modul.   DOI: http://dx.doi.org/10.23960/jpmipa/v24i3.pp658-669